Infiltrasi Budaya Pada Perilaku Ekonomi ¸ Apakah Representasi Nation Threat? - Emma Yunika Puspasari (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
Cultural infiltration can be considered as a threat to the sustainability of Indonesia's local cultural identity and values, so that in this context it can be said to be a